Evaluation of the Anti-Malarial Activity of the Crude Root Extract and Solvent Fraction of Sesamum indicum (Fabaceae) - Girmaw F; Ashagrie G (Dove Medical Press, 2023)
Fentaw Girmaw, Getachew Ashagrie Department of Pharmacy, College of Health Science, Woldia University, Woldia, EthiopiaCorrespondence: Fentaw Girmaw, Department of Pharmacy, College of Medicine and Health Science, Woldia University, P.O. Box 400, Woldia, Ethiopia, Tel +251928383965, Fax +251335400606, Email fentawgirmaw2@gmail.comBackground: A major cumbersome factor in malaria control measure is the new coming antimalarial drug resistance strains. The increase of resistance to the available marketed antimalarial agents dictates the scientific community to search new alternative antimalarial agent from traditional plants. Therefore, our study assesses the antimalarial activity of the crude root extract and solvent fraction of Sesamum indicum in mice.Methods: The roots of Sesamum indicum were extracted by 80% methanol and fractionated using three solvents with different polarities. The in vivo antimalarial activity was assessed at 200 mg/kg, 400 mg/kg, and 600 mg/kg of the root crude extract and solvent fraction using the 4-day suppressive test. Similarly, the n- butanol fraction extract, which showed better suppression potential in 4-day suppressive test from other fractions was also evaluated in the curative model to assess its curative potential. The % parasitemia suppression, mean survival time, body weight change, rectal temperature change, and packed cell volume change were also evaluated in both models.Results: Our finding revealed that the crude extract and solvent fraction treated groups had a statistical significant parasitemia suppression and mean survival time improvement as compared to the negative control (p< 0.001) in both models in a dose-dependent fashion. The higher dose n-butanol fraction treated group (600mg/kg) showed the highest suppression effect and mean survival time prolongation in both tests from the other two fractions. However, the lowest suppressive effect was observed in 200 mg/kg aqueous fraction extract-treated groups in the 4-day suppressive test.Conclusion: The crude root extract and solvent fractions of Sesamum indicum possessed a dose dependent antimalarial activity and a significant change in other parameters in both models that strengthen the traditional claim.Keywords: antimalarial, parasitemia, Plasmodium, Sesamum indicum